Prevalence of red, orange, and green microbial complexes in periodontal pockets of chronic kidney disease patients on hemodialysis: a systematic review and meta-analysis - Diego José Gambin; Jayne de Oliveira Manica; Daniela Dal Olmo Merib; Caroline Mirek; Felipe Gomes Dallepiane; Thais Mageste Duque; João Paulo De Carli; Micheline Sandini Trentin (Bioscience Journal)
To verify the prevalence of specific microorganisms of red, green, and orange microbiological complexes in periodontal pockets of chronic kidney disease (CKD) patients on hemodialysis. This systematic review was conducted according to the PRISMA statement. The search strategy included two independent reviewers who searched the PubMed, Web of Science, Scopus, Cochrane, and Lilacs databases in August 2024, using MeSH terms and keywords defined with the PICOS acronym. The studies included were cross-sectional and published from 2007-2017 in English. The risk of bias and quality of evidence were assessed with the NIH Quality Assessment Tool for Observational Cohort and Cross-sectional Studies. Quantitative analysis with proportion meta-analysis was also performed. 4,737 studies were initially selected, and five were included. The study verified the prevalence of the green complex - Aggregatibacter actinomycetemcomitans (6.69%); the orange complex - Prevotella intermedia (16.85%) and Prevotella nigrescens (37.51%); and the red complex - Treponema denticola (29.11%), Porphyromonas gingivalis (49.45%), and Tannerella forsythia (56.37%), the most predominant microorganism. In the subgingival microbiota of CKD patients on hemodialysis, the red complex showed higher rates and prevalences, and Tannerella forsythia was the most common pathogen.